Concurrent Heat Extremes in Relation to Global Warming, High Atmospheric Pressure and Low Soil Moisture in the Northern Hemisphere - Dalai Nasong; Sha Zhou; Kai Kornhuber; Bofu Yu (Earth's Future)
Abstract Summer heat extremes increasingly co‐occur worldwide, posing disastrous impacts on our society and the environment. However, the spatial pattern and underlying mechanisms of concurrent heat extremes remain unclear. We used a statistical framework to estimate the spatial concurrence strength of heat extremes in the Northern Hemisphere and identified their relationships to global warming, atmospheric circulation, and land‐atmosphere feedbacks. Concurrent heat extremes over different regions have significantly increased in the Northern Hemisphere from 1950 to 2023. Moreover, heat extremes show strong spatial concurrence strength, and the driving factors vary geographically. Global warming is responsible for long‐term increases in the frequency and strength of concurrent heat extremes, with most pronounced impact in tropical regions. In the absence of warming trends, the temporal and spatial variations in concurrent heat extremes are mainly caused by simultaneous high atmospheric pressure controlled by large‐scale circulations, particularly in mid‐latitude regions. While low soil moisture enhances regional heat extremes through land‐atmosphere feedbacks, it plays a minor role in driving concurrent heat extremes alone but can contribute in combination with high‐pressure anomalies. Given the ever‐increasing risks of heat extremes, our study underscores the importance of identifying the mechanisms of spatially concurrent heat extremes to improve prediction and mitigation of widespread heatwaves and their adverse impacts on socio‐economic sustainability and human well‐being.